P220 Evolving role of the respiratory specialist: Pleural ultrasound service 4 years on. (14th November 2013) - Khan, B; Aminy Raouf, H; Mushtaq, M
Abstract : Background: The timely and safe investigation, intervention and management of pleural effusions remains discrepant with varying practices. Following the National Patient Safety Agency 2008 report highlighting 12 deaths from intercostal chest drain, the BTS recommended using ultrasound guidance when inserting chest drains. However, conventionally diagnostic and therapeutic thoracentesis have routinely been performed with either no image guidance or an "X mark the spot" in the radiology department and then transferred back to the ward for the actual procedure. All of these give rise to concern and possibly impact upon quality of care and patient safety. Methods: A retrospective analysis of 4 years experience of providing a Respiratory team delivered ultrasound pleural service; both "inpatient" and "ambulatory". Results: In the 12 months prior to the establishment the pleural service, the radiology department did a total of 96 ultrasounds, of which 46 were "X" marks the spot. Since May 2010, 581 pleural ultrasounds have been performed; with only 5 dry taps and 3 clinically insignificant iatrogenic pneumothoraces. 41% were therapeutic thoracentesis, 26% diagnostic, 18% ultrasound only with no intervention, and 14% pre chest drain insertion or thoracoscopy. "X" marks the spot are now obsolete. Conclusions: Pleural ultrasound has gradually but surely become an essential component of the Respiratory specialist's remit. An inpatient pleural service enables prompt assessment and diagnosis, relief of symptoms and onward management as appropriate. With an ambulatory pleural service, patients with either known malignant pleural effusion or first presentation can be managed as elective daycase procedures without attending A&E or being admitted. Once symptoms are relieved patients are able to go home knowing how to access the Service if the fluid recurs without a crisis admission via A&E. Moreover, unnecessary invasive pleural interventions can be avoided and definitive management expedited. Though requiring appropriate work planning and resources it does result in substantial qualitative and quantitative improvements in patient care. No doubt, not all pleural effusions need be aspirated under ultrasound guidance, however, this is not an exact science and not infrequently, with the aid of pleural ultrasound, an invasive pleural intervention may be avoided altogether.